Investigation of fibrillin microfibrils in the canine cruciate ligament in dogs with different predispositions to ligament rupture. (December 2020) - Cox, T.; Comerford, E.J.; Wegg, M.; Mills, A.; Barrett, S.D.; Smith, K.D.; Sherratt, M.J.; Akhtar, R.
Abstract: Cranial cruciate ligament disease (CCLD) is the most common cause of pelvic limb lameness in dogs but its precise aetiopathogenesis is uncertain. Fibrillin microfibrils (FM) are complex macro-molecular assemblies found in many tissues including ligaments, where they are thought to play an important mechanical role. We hypothesised that FM ultrastructural variation correlates with the differing predisposition of canine breeds to CCLD. Non-diseased cranial and caudal cruciate ligaments (CCLs and CaCLs) were obtained from Greyhound (GH) and Staffordshire Bull Terrier (SBT) cadavers. Fibrillin microfibrils were extracted from the ligaments by bacterial collagenase digestion, purified by size-exclusion chromatography and subsequently visualized by atomic force microscopy (AFM). With AFM, FMs have a characteristic beads-on-a-string appearance. For each FM, periodicity (bead-bead distance) and length (number of beads/FM) was measured. Fibrillin microfibril length was found to be similar for GH and SBT, with non-significant inter-breed and inter-ligament differences. Fibrillin microfibril periodicity varied when comparing GH and SBT for CCL (GH 60.2 ± 1.4 nm; SBT 56.2 ± 0.8 nm) and CaCL (GH 55.5 ± 1.6 nm; SBT 61.2 ± 1.2 nm). A significant difference was found in the periodicity distribution when comparing CCL for both breeds ( P  < 0.00001), further, intra-breed differences in CCL vs CaCL were statistically significant within both breeds ( P  < 0.00001). The breed at low risk of CCLD exhibited a periodicity profile which may be suggestive of a repair and remodelling within the CCL. Highlights: Fibrillin microfibrils are important indicators of canine cruciate disease (CCD) Greyhounds (low risk of CCD) exhibit a unique fibrillin microfibril profile Intra-breed ultrastructural differences between ligaments may explain injury risk